2020
DOI: 10.1515/anona-2020-0150
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of Choquard and singular nonlinearities in fractional Kirchhoff problems

Abstract: The aim of this paper is to study the existence and multiplicity of solutions for a class of fractional Kirchho problems involving Choquard type nonlinearity and singular nonlinearity. Under suitable assumptions, two nonnegative and nontrivial solutions are obtained by using the Nehari manifold approach combined with the Hardy-Littlehood-Sobolev inequality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 47 publications
2
8
0
Order By: Relevance
“…In recent years, the problem of elliptic equations (systems) with critical exponents has attracted the attention of many researchers, and related theory has also made great progress, e.g., results on the existence and nonexistence of nontrivial and multiple solutions were proved, and also some properties of solutions (see [2][3][4][5][6][7][8]). At the same time, in recent years, the problem with critical exponents in fractional elliptic equations, such as fractional Kirchhoff problems and Schrödinger-Kirchhoff-type problems involving the fractional p-Laplacian, have also attracted the attention of researchers (see [9][10][11]).…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…In recent years, the problem of elliptic equations (systems) with critical exponents has attracted the attention of many researchers, and related theory has also made great progress, e.g., results on the existence and nonexistence of nontrivial and multiple solutions were proved, and also some properties of solutions (see [2][3][4][5][6][7][8]). At the same time, in recent years, the problem with critical exponents in fractional elliptic equations, such as fractional Kirchhoff problems and Schrödinger-Kirchhoff-type problems involving the fractional p-Laplacian, have also attracted the attention of researchers (see [9][10][11]).…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…where 𝛾 > 0, 𝑁 ≥ 2𝑠, 𝑠 ∈ (0, 1), 1 < 𝑝 ≤ 2 * 𝜇,𝑠 − 1, and Ω is a smooth bounded domain in ℝ 𝑁 have not been explored in much extent. We cite [38], where the nonlinearity has subcritical growth, authors have proved existence of two positive weak solutions using the Nehari manifold technique. Recently in [36], Sousa et al have shown the existence of a solution for the weighted singular fractional differential problem involving 𝑝-Laplace equation using the Nehari manifold method.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they obtained the existence of infinitely many pairs of entire solutions by genus theory. Wang et al [16] studied the following fractional Kirchhoff equation involving Choquard nonlinearity and singular nonlinearity:…”
Section: Introductionmentioning
confidence: 99%